Pengaruh Kampanye #Yellow Fit Kitchen x Rachel Vennya terhadap Brand awareness Yellow Fit Kitchen - Putri Syayidar Kamal; Riska Tyas Prahesti (Bandung Conference Series: Communication Management, 2023)
Abstract. Public relations can carry out campaign activities, namely by working with celebrity endorsements. This research specifically discusses the influence of the campaign which consists of three indicators, namely message content, message structure and audience response to Brand awareness consisting of knowing the brand, remembering the brand, top brands in memory. This study aims to determine how much influence the Yellow Fit Kitchen x rachel ven campaign has on the Yellow Fit Kitchen brand awareness. The research method uses a quantitative approach with the sampling technique in this study is convenience sampling. Data collection uses non-probability sampling with the criteria of having seen or known the campaign conducted by Yello Fit x Rachel Vennya. The study sample size was calculated by SPSS 25 using the slovin formula and obtained 101 research respondents. Data was collected through online surveys with Google forms and processed using SPSS. The results of this study indicate that the Yellow Fit Kitchen X Rachel Vennya Campaign includes three indicators, namely message content, message structure and audience response which have a strong influence on Yello Fit Kitchen Brand awareness. Abstrak. Public relations dapat melakukan kegiatan campaign yakni dengan bekerja bersama influencer. Dalam penelitian ini dibahas secara spesifik mengenai pengaruh kampanye yang terdiri dari tiga indikator yakni isi pesan, struktur pesan dan respon khalayak terhadap brand awareness terdiri dari mengenal merek, mengingat merek, merek teratas dalam ingatan. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh kampanye Yello Fit Kitchen x Rachel Vennya terhadap brand awareness Yello Fit Kitchen. Metode penelitian menggunakan pendekatan kuantitatif dengan teknik sampling dalam penelitian ini adalah convenience sampling. Pengumpulan data menggunakan non probability sampling dengan kriteria pernah melihat atau mengetahui kampanye yang dilakukan Yello Fit x Rachel Vennya. Ukuran sampel penelitian dihitung dengan SPSS 25 menggunakan rumus slovin dan diperoleh 101 responden penelitian. Data dikumpulkan melalui survey online dengan google form dan diolah menggunakan SPSS. Hasil penelitian ini menunjukan bahwa kampanye Yellow Fit Kitchen X Rachel Vennya mencakup tiga indikator yaitu isi pesan, struktur pesan dan respon khalayak memiliki pengaruh kuat terhadap brand awareness Yellow Fit Kitchen.